Outcomes of Newborns with Tracheo-Esophageal Fistulas (Tef) in Combined Military Hospital, Peshawar - Murtaza, Shumaila; Shah, Syed Awais ul Hassan; Razzaq, Asma; Ibrahim, Sadaf; Ahmad, Shakeel (Pakistan Armed Forces Medical Journal, 2026)
Objectives: To determine the incidence of various outcomes in neonates with Tracheo-Esophageal Fistulas (TEF) after surgery and to evaluate the risk factors associated with mortality.Study Design: Prospective cohort study.Place and Duration of Study: Department of Pediatrics, Combined Military Hospital (CMH), Peshawar Pakistan, Jan 2023 to Aug 2024.Methodology: This study was conducted after enrolling 31 neonates with TEF diagnosed via clinical, radiographic, and/or endoscopic findings. Neonates with fatal chromosomal anomalies incompatible with life, those who did not undergo surgical correction or were lost to follow-up were excluded. All patients underwent surgical correction of the defect and were managed post-operatively in the neonatal intensive care unit (NICU). Post-discharge, they were followed at regular intervals for one year to check for the development of complications.Results: Of the 31 patients studied, most were males (n=18, 58.10%). The most common fistula seen was Type C, accounting for 25(80.60%) cases. Patent ductus arteriosus was the most common type of cardiac anomaly seen (n=5, 16.10%), and cardiac anomalies were more commonly seen in patients who died (p=0.01). Duration of mechanical ventilation was higher in patients who died:  69.00 (IQR: 29.00) hours versus 48.00 (IQR: 37.00) hours, (p=0.06). Pneumothorax (p